Direct costs of unintended pregnancy in Spain. (August 2015) - Lete, Iñaki; Hassan, Fareen; Chatzitheofilou, Ismini; Wood, Eifiona; Mendivil, Joan; Lambrelli, Dimitra; Filonenko, Anna
Abstract: Objective The aim of the study was to estimate the burden and direct medical costs of unintended pregnancy to the public payer in Spain. Methods An economic model evaluating the costs and outcomes of contraceptive use over a 1-year period was constructed for women in Spain aged 15 to 44 years at risk of pregnancy. Model inputs were derived from published literature and national survey data. Outcomes evaluated included: (i) the annual number of unintended pregnancy events and their cost; (ii) the proportion of unintended pregnancy events and their cost due to non-adherence; and (iii) the use and cost of contraceptive methods in Spain. Results Of the total number of pregnancies, 35% are estimated to be unintended and are associated with a direct cost burden of €292.8 million per year. Most unintended pregnancies (26%) occur in women aged 30 to 34 years, whilst 69% of the total cost burden is estimated to be attributable to poor adherence to contraceptive methods. Conclusions The cost associated with unintended pregnancy is high. The major proportion of the burden is estimated to be attributable to imperfect adherence and is likely avoidable. Shifts in patterns of contraceptive use, combined with measures to improve adherence, could have a substantial and positive impact on this burden. Chinese Abstract 摘要： 目的 本研究目的是估算在西班牙意外妊娠给公众纳税人带来的负担和直接医疗费用。 方法 针对西班牙15至44岁有妊娠风险的女性建立一个经济模型，来评价采用避孕措施超过1年的费用和效果。模型的数据的纳入来自公开发表的文献和国家调查数据。效果评价包括以下内容：（1）一年意外妊娠事件的数目和相关费用；（2）由于未坚持使用避孕措施而意外怀孕事件的比例和相关费用；（3）在西班牙避孕措施的应用及相关费用。 结果 在总的怀孕人数中，约35%是意外妊娠，与之相关的直接费用负担是每年2.928亿欧元。意外妊娠发生率最高的是30-34岁妇女，为26%，同时，据估算，总费用负担的69%是由于没有很好的坚持使用避孕方法。 结论 意外怀孕相关的费用很高。负担的最主要的部分是由于没有很好地坚持采用避孕措施造成，并且这可能是可以避免的。改变避孕方法应用的模式，同时采取一些提高依从性的措施，能够对降低负担产生重大的积极的影响。